The Communication Mechanism in a Distributed System: Zain Ali - Zain ali, Zain ali (International Journal for Electronic Crime Investigation, 2021)
In this research, problems are discussed dynamically distributed systems that relate to the sharing of data and communication from one system to another over the network. A distributed system communicates with its related systems by sending and receiving messages over the internet and in this way, it fulfills its work. When we discuss dynamic distributed systems, it means that it includes many different changeable types of networks, different operating systems like android, mac, windows, different software processors portability, breaking down of WAN, and inter-process communication errors. Another problem that accrues in distributed systems is latency. So, it is very difficult to develop software for these types of environments. Proposed work is related to make message communication in distributed systems easy, reliable, and efficient. For the sharing of data, coherence is responsible. Every problem can be solved but that proper appropriate methods and algorithms are required. We create a new method which is a dynamic atomic shared memory for message communication. A properly stated method is proposed for message communication and then implemented. According to this method, owners can be changed dynamically and their access to read and write also changes.